The Local Initiator Role in the Adoption of Biogas Energy Innovation for Household Needs in Rural Areas - Hartiningsih, Hartiningsih (Jurnal Bina Praja, 2016)
The need for Kerosene is very high. When energy crisis hit Indonesia, it caused the scarcity and soaring prices of kerosene. Hence, finding alternative energy sources is needed, especially a renewable energy to households. One is which is Biogas energy. Biogas is an energy that uses simple technology, which uses raw materials of animal waste. Many rural communities do not know about it, so it requires a pioneer, called the local initiator. The local initiator is an agent of change that comes from the local community, who has the initiative to make changes and become a guide passage of the change process in an organization or community, in order to achieve the expected goals. Local initiator becomes an important factor in the success of biogas innovation adoption. Biogas is used for household needs such as cooking, water heating, and lighting. Biogas program has been reinforced by Presidential Decree No 5 of 2006, Minister of ESDM Regulation (Permen ESDM) No 3 of 2013, Permen ESDM No 10 of 2015, and Minister of Rural Affairs Regulation (Permen Desa) No 5 of 2015. This paper aims to examine the role of a local initiator as an agent of change and the most dominant factors in the successful adoption of biogas for the needs of rural households. This study uses a qualitative method by using a case study approach and conducting a descriptive analysis. The focus of the data analysis is only performed on the local initiator in the successful adoption of biogas in Haurngombong village in West Java and Pandua-North Lombok, NTB. The result of the study shows that the successful adoption of biogas in Haurngombong Village and Pandua Village is strongly influenced by the local initiator. The local initiator success is not determined by the position, age, and gender, but is determined by the experience in the use of biogas, biogas sector knowledge, dissemination strategies, and communication among stakeholders of biogas program. The key to the success of local initiators in the adoption of biogas innovation lies in good communication with the public.